The Role of Defense Science Philosophy in Determining Strategies to Maintain The Sovereignty and Integrity of The Unitary State of The Republic Indonesia in Industrial Revolution 4.0 - Junita Dewi Sari Simanjuntak; Timbul Siahaan; George Royke Deksino; Nadya Ophelia (CV. AFDIFAL MAJU BERKAH, 2024)
The complexity and dynamics of this era, the philosophy of defense science becomes a conceptual guide in formulating appropriate strategies. This research used a qualitative descriptive method. Through qualitative descriptive methods, this research analyzes the role of defense science philosophy in determining strategies to maintain the sovereignty and integrity of unitary state of the Republic of Indonesia. Industrial Revolution 4.0 brings the potential to increase the country's defense capabilities, but also brings new threats, especially in terms of cyber security and paradigm changes in social and economic life. From the research that had been carried out, researchers found that the philosophy of defense science is the basis for understanding basic values, principles and concepts in determining strategies to maintain the sovereignty and integrity of the Republic of Indonesia in the era of industrial revolution 4.0 in conceptual analysis, defense ethics and ethos, threat identification, social studies and politics, as well as the development of critical thinking and innovation. Based on the role of the defense science philosophy, strategies were found to maintain the sovereignty and integrity of the Republic of Indonesia, which includes strengthening cyber security, maritime defense, developing artificial intelligence, increasing human resource capabilities, international collaboration, and increasing public awareness and education. By using this approach, the philosophy of defense science contributes significantly protecting the Republic of Indonesia from growing threats in an era of rapidly developing technology.